PENGARUH STRATEGI DIVERSIFIKASI DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Inayah Adi Sari; Adi Wiratno; Eko Suyono (Master of Accounting Universitas Trunojoyo Madura, 2014)
The purpose of this study is to empirically study the effect of diversification strategy and firm characteristic to firm value. The population used in research were all the manufacture companies registered in BEI during the period 2006-2008. The samples used in research were 102 companies. Independent variable used in research were diversivication level, leverage, earning growth, size, age, price to book value, and return on asset and Dependent variable was excess value. The result of this study using compare mean analysis finds that there is no different of excess value from single segment company and multy segment company. The result of this study using multiple regression finds that only two variables (diversification level and size) that significantly affect the excess value with level of significance 5 percent